Objeto de aprendizagem para o ensino do efeito fotoelétrico no ensino fundamental - Santos, Alexandre da Silva (2016)
Teaching-learning physics processis a challenge in Brazil and the world. Currently, there is a consensus of the existence of a great difficulty in teaching physics at all levels of education. Teachers complain mainly of disinterest, lack of student motivation to learn physics, besides the widespread practice of finding schoolsteaching physicsby teachers who do not have a degree in physics, the number of physics teacher are insufficient and the quality of their formation often are questioned. These factors undoubtedly have hindered the ways to bring the physics contents to the classroom, and especially those related to modern and contemporary physics. The photoelectric effect is a phenomenon of modern physics and we can see it, in the day to day functioning of the doors of malls, in public lighting system, alarm systems, among others. In this work an educational software for PC or learning object, in form of a game about the photoelectric effect was developed in Java programming language. The main objective was to motivate the student to learn some concepts of contemporary physics, and thus provide a significant learning basics of the photoelectric effect, according to Ausubel's theory. The learning object consists of a data-sheet explain the stages of the game, some evaluation questions, which should be learned the basics of the photoelectric effect. Before and after using the software by student’s questionnaires were applied to assess the level of learning these concepts and motivation for learning science. A teaching and learning strategy using the LO was applied to a class of ninth year of elementary school in a public school from the city of Lauro de Freitas, Bahia. From the analysis of the results we can say that the application of LO in students of elementary school, generated a certain level of learning of the subjects on the photoelectric effect. At the same time, it was observed an increase in average student motivation index. The Cronbach's alpha was 0.86, showing a high value of reliability of data from the questionnaires. We highlight that the application of educational product, the proposed learning strategy, proved valid and suggest its use for teaching and motivation of elementary school students in learning some concepts of Contemporary Physics and Modern, through the photoelectric effect.